Pengaruh Pendekatan Pembelajaran Mendalam terhadap Kemampuan Spasial Matematis Siswa Kelas IX - I Gusti Ngurah Gede Bayu Prajna Nugraha; I Gusti Nyoman Yudi Hartawan; I Gusti Putu Suharta (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Students' mathematical spatial abilities are still relatively low, especially in geometry. This study aims to analyze the effect of an immersive learning approach on students' mathematical spatial abilities. The study used a quasi-experimental design with a posttest-only control group design. The study population was all ninth-grade students of SMP Negeri 1 Mendoyo, with a sample selected using cluster random sampling technique, consisting of an experimental class and a control class. Data were collected through a mathematical spatial ability test and analyzed using descriptive statistics and an independent sample t-test. The results showed that the average mathematical spatial ability of students in the experimental class (88.59) was higher than that of the control class (61.41). Prerequisite tests showed that the data were normally distributed and homogeneous. The t-test results showed a significance value <0.05, indicating a significant difference between the two groups. Thus, the immersive learning approach proved effective in improving students' mathematical spatial abilities and had a significant effect, making it suitable for application as an alternative in mathematics learning in geometry.